INTRODUCING ENGLISH TO EARLY CHILDHOOD THROUGH SINGING WITH THE TOTAL PHYSICAL RESPONSE METHOD - Septi Gumiandari (Acitya: Journal of Teaching and Education, 2021)
Introducing English from an early age should be supported by adequate media and infrastructure. Learning should be arranged in such a way as to give birth to learning activities that are important and fun. Therefore, it requires perfect and efficient teaching methods. Research on "Introducing English to early childhood through singing with the TPR method" aims to introduce English by singing to early childhood at al-Hidayah Kindergarten, Greged District, Cirebon. The method used is a descriptive analysis of activities carried out by fostering the ability to recognize English in early childhood. The process is carried out using several methods such as singing while playing and singing, with movements using learning media. The conclusion is that by using the singing and playing method, early childhood children can easily recognize the vocabulary, and can accidentally add to the vocabulary of the child.